Antagonistic Action of Streptomyces Sp. On Rhizoctonia bataticola, a Common Soil Borne Pathogen of Forest Nurseries - Kulkarni, Srikant; Siddaramaiah, A. L.; Basavarajaiah, A. B. (Indian Forester, 1980)
no abstract